2017
DOI: 10.3389/fmats.2017.00015
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Nutrient Used in Biogenic Healing Agent for Cementitious Materials

Abstract: Biogenic self-healing cementitious materials target on the closure of micro-cracks with precipitated inorganic minerals originating from bacterial metabolic activity. Dormant bacterial spores and organic mineral compounds often constitute a biogenic healing agent. The current paper focuses on the investigation of the most appropriate organic carbon source to be used as component of a biogenic healing agent. It is of great importance to use an appropriate organic source, since it will first ensure an optimal ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 11 publications
1
16
0
1
Order By: Relevance
“…In two recent studies, the effect of organic calcium salts, which can act as calcium carbonate mineral precursor compounds (calcium and sodium gluconate, calcium acetate and calcium lactate), were investigated for potential to heal cracks in mortar specimens, and it was found that calcium gluconate and calcium lactate enhance the self‐healing kinetics for large cracks, and that the compressive strength of mortar cubes increased with 8% for calcium lactate and with 13.4% for calcium acetate …”
Section: Self‐healing Bioconcretementioning
confidence: 99%
“…In two recent studies, the effect of organic calcium salts, which can act as calcium carbonate mineral precursor compounds (calcium and sodium gluconate, calcium acetate and calcium lactate), were investigated for potential to heal cracks in mortar specimens, and it was found that calcium gluconate and calcium lactate enhance the self‐healing kinetics for large cracks, and that the compressive strength of mortar cubes increased with 8% for calcium lactate and with 13.4% for calcium acetate …”
Section: Self‐healing Bioconcretementioning
confidence: 99%
“…Several strategies have been described that utilize bacteria as a self-healing agent capable of surviving the harsh environment of concrete mixing. [245][246][247][248][249][250] These strategies typically utilize concrete matrices mixed with immobilized bacterial strains. Bacteria are capable of converting calcium lactate into calcium carbonate by using external oxygen.…”
Section: Other Applications Of Stimuli-responsive Elmsmentioning
confidence: 99%
“…3 This leads to recovery in transport properties and hence durability performance and, to some extent, to recovery in mechanical properties. Several methodologies have been applied to achieve such self-healing, including the enhancement in the autogenous capacity of cementitious materials to heal their own cracks through the addition of minerals, 4,5 fibres, 6 superabsorbent polymers (SAPs), 7 ; and autonomic healing through vascular systems, 8,9 bacteria [10][11][12] and shape memory polymers. 13 However, the addition of these materials may lead to unwanted variations in the rheology during mixing and/or laborious changes to include the system during casting.…”
Section: Introductionmentioning
confidence: 99%